MultipliCidades da favela - Noronha, Nayara Silva de (2017)
In this dissertation, I analyze how the social space in Heliópolis’ favela is organized. I utilize ethnographic insights and grounded theory as research strategies, based on the social constructionism approach. The data collection method was an 18-month participant observation, from ethnographic fieldwork. Besides the field notes, I also used as part of my analysis: 7 minutes of local meetings, 13 semi-structured interviews, 8 open interviews, 26 testimonials on the project “Memória de Heliópolis” and 2 WhatsApp groups. Following the grounded theory, the data analysis consists in examining 9 categories and 29 subcategories found in the fieldwork. I found that the social space in Heliópolis is, in fact, a complex multidimensional organizational environment, and such aspects as cultural, political, urbanistic and market must be taken into consideration. That said, the intricacy and interaction of these different aspects led me to understand that it is not possible to reduce the favela to precariousness only – even though it might be one of the facets present in some way into this space. The heterogeneity found in Heliopolis made me realize that this image of a favela as a static space which is apparently forgotten by the State and society does not exist in reality. Heliopolis is a space in constant movement – a movement not only made by people or objects, but also by these dimensionalities that constantly complement, overlap, modify, and contradict each other. Thus, in highlighting Heliópolis’ multidimensional sociospatial organization structure, this dissertation aims to contribute in helping scholars to see favelas as an totality of urban space.